(untitled) (Applied Biological Research, 2019)
A field experiment was conducted at research farm of PAU, Ludhiana, Punjab (India) for consecutive three years (2015-2017) to study the effect of foliar application of different nutrients at early reproductive stage (R3 stage) on growth, productivity and profitability of soybean. The experiment comprised of eight treatments of foliar nutrient application at pod initiation stage along with the recommended dose of fertilizer (RDF). The treatments were: water spray, urea 2% spray, diammonium phosphate (DAP) 2% spray, muriate of potash (MOP) 0.5% spray, NPK 19:19:19 (N:P2O5:K2O) 2% spray, molybdenum 0.1% spray, zinc chelated 0.5% spray and no spray (control). Results revealed that different treatments of foliar nutrients did not significantly influence the growth attributes; however, foliar application of 2% urea yielded significantly higher number of pods plant-1than other treatments and was at par with RDF + 0.5% MOP. Foliar application of 2% urea also gave the highest seed yield, gross returns and net returns and was statistically at par with spray of 0.5% MOP, 2% DAP, 0.5% chelated zinc and 0.1% molybdenum (except net returns). It may be concluded that foliar application of 2% urea at pod initiation stage provides highest seed yield, gross returns, net returns and B:C ratio.